2022
DOI: 10.3390/polym14132661
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Reprocessing with a Quad Screw Extruder on the Degradation of Polypropylene

Abstract: During mechanical recycling, polypropylene typically is reprocessed using a single- or twin-screw extruder. The degradation of polypropylene during this reprocessing reduces the polymer’s molecular weight and, consequently, limits the performance of the recycled resin. This work investigated the impact of a quad screw extruder (QSE), which has greater free volume, on the reprocessing of an impact copolymer polypropylene. To mimic the recycling process, the polypropylene was subjected to three processing cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…In the case of PP, the images (Figure 8a,b) are almost identical too, as also reported by Tochacek et al [47,52], who under increased magnification and after extraction with heptane were able to compare the size of the rubbery phase and noted there was no decrease in particle size with multiple processing. This observation by Tochacek et al was in contradiction to the work performed by Alotaibi et al [49] where the ethylene propylene rubber (EPR) of heterophasic PP was visible and, with each reprocessing step, the EPR steadily decreased in size, which is also similar to the observations of Bouaziz et al [73].…”
Section: Morphological Properties: Analysis Of the Surface Morphology...mentioning
confidence: 69%
See 2 more Smart Citations
“…In the case of PP, the images (Figure 8a,b) are almost identical too, as also reported by Tochacek et al [47,52], who under increased magnification and after extraction with heptane were able to compare the size of the rubbery phase and noted there was no decrease in particle size with multiple processing. This observation by Tochacek et al was in contradiction to the work performed by Alotaibi et al [49] where the ethylene propylene rubber (EPR) of heterophasic PP was visible and, with each reprocessing step, the EPR steadily decreased in size, which is also similar to the observations of Bouaziz et al [73].…”
Section: Morphological Properties: Analysis Of the Surface Morphology...mentioning
confidence: 69%
“…As a lot of work has been conducted on the reprocessing of PP already and only four papers from Alotaibi et al [49], Hermanova et al [50] and Tochacek et al [51,52] dealt with the recycling and characterization of impact copolymer polypropylene (ICPP), we decided to compare PHB with ICPP. Tochacek et al [47] studied the degradation of ICPP over multiple extrusion cycles and concluded that the degradation behavior is similar to PP as it constitutes around 90% of the mass of the polymer with the effect of the rubbery fraction more pronounced with regard to fracture behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include beverage cup lids, lunchboxes, frozen liner boxes, and food packaging materials such as plastic cutlery. Extrusion molding [ 9 ], which utilizes an extruder [ 10 ], involves thoroughly mixing and heating plastic fiber or sheet-like polymer raw materials to form sheets. These molten sheets or film materials are then continuously heated and vacuum-formed through aluminum alloy molds [ 11 ] or shaping modules [ 12 ], followed by cooling and cutting to produce various products.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies in laboratory environments were already carried out to address this topic. The main results are an increasing MFR, a decreasing ductility, and a drop in the oxidation induction temperature, which corresponds to a decreased molecular weight [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%